Old Testament Theology Its history & development - Hayes, John H. (Atlanta John Knox Press, 1985)
John Hayes and Frederick Prussner offer a thorough study covering the history, methodologies, and difficulties that are associated with the writing of Old Testament theology. Their impressive work features comprehensive history, summaries, contemporary is
Keywords: Bible. -- Old Testament -- Theology. Bible. -- A.T. -- Théologie -- Histoire. Bible. -- Old Testament. Bible. -- Old Testament -- Doctrines -- History. Bible -- Theology. Theology. Theology, Doctrinal -- History